Antropologia e museus reciprocidades: o caso do Museu do Índio - Sandra Martins Farias (2008)
Anthropology, heritage and museums have beginning them emergence throughout the colonial expansion, but and they consolidated during the XIX century. During these almost two centuries of existence had moments of deep and profuse reciprocity and others of great estrangement. In the Brazilian case the relationships among these areas also followed thissame oscillation. The present work aims to present some of these moments of close approximate, having as background the study of one ethnographic museum: the Museum of the Indian. The proposalhere worked is to identify and to establish the strategies that the Museum of the Indian establishes and how they act while a bridge of two hands in the relationship between museum and anthropology. In this sense, the pretension of this study is to identify the interlacements betweenanthropology and museums in certain period of the it disciplinary / scientific history of both, having as objective of this interactivity the Museum of the Indian, how it comes to contribute inside for the debate and the strengthen of studies on themes of the heritage and museums ofthe anthropological science.